The KLK5 protease suppresses breast cancer by repressing the mevalonate pathway - Pampalakis, Georgios (Impact Journals LLC, 2013)
Kallikrein-related peptidase 5 (KLK5) displays aberrant expression in cancer. However, any functional association is missing. Here, we show that reconstitution of KLK5 expression in non-expressing MDA-MB-231 breast cancer cells suppresses malignancy in vitro and in vivo dose-dependently. Reactivation of KLK5 suppressed key EMT genes. Unexpectedly, we identified altered expression of genes encoding enzymes of the mevalonate pathway typical of those observed upon cholesterol starvation. Consistently, we found that SREBF1, the master regulator of the mevalonate pathway was induced. KLK5 re-expression leads to reduced cellular cholesterol and fatty acid synthesis and enhanced uptake of LDL-cholesterol. Suppression of the mevalonate pathway in KLK5 transfectants was further shown by reduced synthesis of isoprenoids. Indeed, we found diminished levels of active RhoA, a signaling oncoprotein that requires prenylation for activation. We propose that reduced RhoA activation plays a dominant role in suppression of malignancy by KLK5, since geranylgeranyl pyrophosphate restored active RhoA in KLK5-reverted cells resulting in increased malignancy. For the first time, we suggest that a protease may suppress breast cancer by modulating the mevalonate pathway.